2014
DOI: 10.1016/j.nurpra.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Primary-Care Providers on Perceived Benefits of and Barriers to PainTracker

Abstract: Management of chronic pain is a common and complex challenge in primary care. Patient-reported outcomes surveys can help assist the patient with chronic pain to communicate the symptoms to their provider and engage the patient in treatment planning and evaluation to improve both quality of care and patient outcomes. A web survey was used to assess clinic providers’ perceived ease of use, barriers to use, and clinical benefits of a patient-reported outcomes survey, termed PainTracker. More than half the respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…Stage One, n  = 202, Stage Two, n  = 60, stage Three, n  = 253 (medical and surgical patients)Descriptive statisticsRavaud et al [45]FranceCluster-randomised controlled trial; outcome measures, patients’ medical recordTo evaluate the impact of an educational programme for nurses to improve pain assessmentVisual Analogue Scale—pain intensitySurgical wards. n  = 2278 surgical patientsMixed-model ANOVASchorn et al [35]USACross-sectional analytic; surveyTo assess how well a tool for pain measurement is received by healthcare providersPEG (3-item version of the Brief Pain Inventory)*—pain intensity and interferences, Patient Health Questionnaire (PHQ-4)*—depression and anxiety, Generalised Anxiety Disorder (GAD-7)*—anxietyPrimary care. n  = 30 primary care providersQuantitative data—descriptive statistics, qualitative data—content analysisStratford and Binkley [40]CanadaCase series; patient-reported outcome measuresTo demonstrate the application of the Roland-Morris questionnaire in clinical scenarios can aid decision-making in clinical practiceRoland-Morris Questionnaire*—disabilityPhysical therapy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Stage One, n  = 202, Stage Two, n  = 60, stage Three, n  = 253 (medical and surgical patients)Descriptive statisticsRavaud et al [45]FranceCluster-randomised controlled trial; outcome measures, patients’ medical recordTo evaluate the impact of an educational programme for nurses to improve pain assessmentVisual Analogue Scale—pain intensitySurgical wards. n  = 2278 surgical patientsMixed-model ANOVASchorn et al [35]USACross-sectional analytic; surveyTo assess how well a tool for pain measurement is received by healthcare providersPEG (3-item version of the Brief Pain Inventory)*—pain intensity and interferences, Patient Health Questionnaire (PHQ-4)*—depression and anxiety, Generalised Anxiety Disorder (GAD-7)*—anxietyPrimary care. n  = 30 primary care providersQuantitative data—descriptive statistics, qualitative data—content analysisStratford and Binkley [40]CanadaCase series; patient-reported outcome measuresTo demonstrate the application of the Roland-Morris questionnaire in clinical scenarios can aid decision-making in clinical practiceRoland-Morris Questionnaire*—disabilityPhysical therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Clinicians from various backgrounds, including physicians, nurse practitioners, and physical therapists, suggested that the purpose of PROMs was to assess the patients’ pain and quantify the impact of their pain [34, 35]. PROM data were also seen as a useful way to view pain within the context of a patients’ life [36, 37]; illustrated in the following quote from a nurse using PROMs in a hospital setting: It is important to assess and take into account the thresholds of physical pain for each different individual on different occasions and how it is impacted by cultural and physiological factors [37].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations